Changes in the Prevalence of Metabolic Syndrome, Its Components, and Relevant Preventive Medication between 2011 and 2018 in the Northeast Hungarian Roma Population - Piko, Peter (J Pers Med, 2021)
Metabolic syndrome (MetS) is a cluster of clinical conditions that poses a major health burden worldwide. In the present study, we investigate the changes in the prevalence of MetS and its components among the Roma in two disadvantaged counties in Northeastern Hungary focusing on a seven-year-long period. The database of the present study is based on cross-sectional surveys of the Hungarian Roma population (aged 20–64 years) conducted in 2011 (n = 458) and 2018 (n = 374). The increase in the prevalence of MetS itself in the whole Roma population was not found to be significant in the period examined (although it increased from 40.0% up to 46.0%, p = 0.080); however, regarding its components, there was a significant increase in the prevalence of central obesity (from 62.7% to 73.3%, p = 0.001) and raised blood pressure (BP) or treated hypertension (from 45.2% to 54.5%, p = 0.007). These changes were mainly observed in the younger age groups, so the risk for MetS increased significantly in the 20–34 (OR = 1.10, p = 0.038) and 35–49 (OR = 1.07, p = 0.048) year age groups in the 2018 study population compared the 2011 one. The increasing prevalence of hidden hypertension and, consequently, untreated individuals with raised BP (from 29.6% to 43.5%, p = 0.014) among females is quite alarming; therefore, a targeted public health strategy and targeted interventions are desperately needed to prevent further worsening of the current situation.